The Role of CARD9 Deficiency in Neutrophils - Sheng, Ruanmei (Mediators Inflamm, 2021)
Neutrophils play a critical role in innate immune defense and directly contribute to infectious and autoimmune ailments. Great efforts are underway to better understand the nature of neutrophilic inflammation. Of note, CARD9, a myeloid cell-specific signaling protein that mainly expresses in macrophages and dendritic cells, is also present in neutrophils, emerging as a critical mediator for intercellular communication. CARD9–deficiency neutrophils display an increased susceptibility to fungal infection that primarily localize to the central nervous system, subcutaneous, and skin tissue. Additionally, CARD9–deficiency neutrophils are associated with some autoimmune diseases and even provide protection against a few bacteria. Here, the review summarizes recent preclinical and clinical advances that have provided a novel insight into the pathogenesis of CARD9 deficiency in neutrophils.